2016
DOI: 10.1016/j.hpb.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day outcomes underestimate endocrine and exocrine insufficiency after pancreatic resection

Abstract: Reporting 30-day functional outcomes for pancreatic resection is insufficient, as nearly 45% of subjects who develop disease do so after 90 days. Reporting of at least 90-day outcomes may more reliably assess risk for post-operative endocrine and exocrine insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 29 publications
3
36
0
3
Order By: Relevance
“…Multivariate analysis conducted by Kwon et al in a study population of 225 patients found that patients who were obese (BMI ≥ 25) had increased risk of developing DM post pancreatectomy (OR 1.25; (95% CI: 1.09‐1.43; P = .001). No significant differences were found in the incidence of obesity between DM and non‐DM groups in the remaining studies that assessed for this …”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…Multivariate analysis conducted by Kwon et al in a study population of 225 patients found that patients who were obese (BMI ≥ 25) had increased risk of developing DM post pancreatectomy (OR 1.25; (95% CI: 1.09‐1.43; P = .001). No significant differences were found in the incidence of obesity between DM and non‐DM groups in the remaining studies that assessed for this …”
Section: Resultsmentioning
confidence: 82%
“…Although Wu et al found that of the 3914 patients who did not have pre‐existing diabetes, those with chronic pancreatitis had a significantly higher risk of postoperative DM after multivariate analysis ( P = .001), in five other studies the preoperative pancreatic diagnosis was not predictive of postoperative diabetes risk …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations